2009
DOI: 10.2337/db08-1054
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Depot Differences in Adipocyte Insulin Sensitivity and Glucose Metabolism

Abstract: OBJECTIVETo investigate how insulin sensitivity and glucose metabolism differ in adipocytes between different fat depots of male and female mice and how sex steroids contribute to these differences.RESEARCH DESIGN AND METHODSAdipocytes from intra-abdominal/perigonadal (PG) and subcutaneous (SC) adipose tissue from normal, castrated, or steroid-implanted animals were isolated and analyzed for differences in insulin sensitivity and glucose metabolism.RESULTSAdipocytes from both PG and SC depots of females have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
294
5
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 357 publications
(341 citation statements)
references
References 35 publications
37
294
5
5
Order By: Relevance
“…We verified the hypothesis (see Introduction) that the capacity for enlargement is increased in adipocytes of female compared with male mice in response to a long-term HF feeding, possibly reflecting the higher insulin sensitivity of the female adipocytes. In contrast to similar studies performed previously, 6,7,19 the sex-dependent metabolic phenotypes observed in this mouse model of dietary obesity could not be attributed to a lower body weight gain, adiposity and/or smaller fat cells in females. Most of the results were confirmed by an independent experiment on a separate cohort of animals (not shown).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We verified the hypothesis (see Introduction) that the capacity for enlargement is increased in adipocytes of female compared with male mice in response to a long-term HF feeding, possibly reflecting the higher insulin sensitivity of the female adipocytes. In contrast to similar studies performed previously, 6,7,19 the sex-dependent metabolic phenotypes observed in this mouse model of dietary obesity could not be attributed to a lower body weight gain, adiposity and/or smaller fat cells in females. Most of the results were confirmed by an independent experiment on a separate cohort of animals (not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…Human 1,2 as well as animal studies [3][4][5][6][7] demonstrate less severe obesity-related metabolic disorders including peripheral tissue insulin resistance and dyslipidemia (i.e., the components of metabolic syndrome), and/or later onset of these adverse phenotypes in female than in male subjects. However, mechanisms underlying a relatively low susceptibility of females to metabolic syndrome remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estrogen regulates glucose and lipid metabolism by acting on various target tissues. It has been shown to increase insulin sensitivity and suppress de novo lipogenesis in adipose tissue, the liver and skeletal muscle (Takeda et al 2003, D'Eon et al 2005, Nagira et al 2006, Macotela et al 2009). It also reportedly enhances cholesterol uptake and suppresses gluconeogenesis in the liver (Bryzgalova et al 2006).…”
Section: Introductionmentioning
confidence: 99%